1999
DOI: 10.1590/s0100-879x1999001100009
|View full text |Cite
|
Sign up to set email alerts
|

Role of nitric oxide in hypoxia-induced hyperventilation and hypothermia: participation of the locus coeruleus

Abstract: Hypoxia elicits hyperventilation and hypothermia, but the mechanisms involved are not well understood. The nitric oxide (NO) pathway is involved in hypoxia-induced hypothermia and hyperventilation, and works as a neuromodulator in the central nervous system, including the locus coeruleus (LC), which is a noradrenergic nucleus in the pons. The LC plays a role in a number of stress-induced responses, but its participation in the control of breathing and thermoregulation is unclear. Thus, in the present study, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 30 publications
(34 reference statements)
1
18
0
Order By: Relevance
“…The effect of icv injection of kynurenic acid and MCPG on the ventilatory response to hypoxia observed in the current study resembles the effect observed after icv injection of L-NAME (a nonselective nitric oxide synthase blocker) (23). In fact, activation of brain L-glutamate has been shown to lead to synthesis and release of nitric oxide (24,25) and Ogawa et al (26) have suggested a possible interaction between L-glutamate and nitric oxide in the CNS in the control of breathing during hypoxia.…”
Section: Ventilatory Response To Hypoxiasupporting
confidence: 75%
See 1 more Smart Citation
“…The effect of icv injection of kynurenic acid and MCPG on the ventilatory response to hypoxia observed in the current study resembles the effect observed after icv injection of L-NAME (a nonselective nitric oxide synthase blocker) (23). In fact, activation of brain L-glutamate has been shown to lead to synthesis and release of nitric oxide (24,25) and Ogawa et al (26) have suggested a possible interaction between L-glutamate and nitric oxide in the CNS in the control of breathing during hypoxia.…”
Section: Ventilatory Response To Hypoxiasupporting
confidence: 75%
“…L-glutamate may act mainly in the brain stem areas associated with respiration (such as nucleus tractus solitarii and ventrolateral medulla) and dopamine may mainly act by stimulating central areas (such as the hypothalamus) involved in thermoregulation, leading to respiratory, thermal and metabolic adjustments during hypoxia exposure. Yet, some other modulators released during hypoxia exposure in the CNS may have effects on both respiratory and thermoregulatory systems, such as adenosine (36) and nitric oxide (23), which attenuate hypoxic hyperventilation and anapyrexia.…”
Section: Thermoregulatory Response To Hypoxiamentioning
confidence: 99%
“…It is estimated that~50% of all the noradrenergic projections in the central nervous system originate in the LC [8,13]. Consequently, LC is implicated not only in the control of breathing [16,20,29,32,47,64] but also in the control of many homeostatic functions including thermoregulation [2,21,53] and cardiovascular function [3,40,41,61,65].…”
Section: Introductionmentioning
confidence: 99%
“…An interesting hypothesis is that hypercapnia, acidosis, or both may affect the activity of neurons controlling the efferent heat loss and heat production pathway for thermoregulation such as those present in the preoptic hypothalamic area [67]. The LC has been shown to participate in the efferent neuronal pathway controlling thermogenesis during fever [2], and there is evidence that this nucleus is also involved in the hypoxia-induced regulated hypothermia [21].…”
Section: Introductionmentioning
confidence: 99%
“…Hypoxia reflexively increases pulmonary ventilation by activating peripheral chemoreceptors, particularly in the carotid bodies (CB) (Taylor et al, 1999). Recent studies using in vitro models have demonstrated that endogenous gaseous compounds, such as CO, play an important role in modulating this hypoxia-induced excitation of chemoreceptors (Fabris et al, 1999(Fabris et al, , 2000Prabhakar, 1995Prabhakar, , 1999Prabhakar, , 2000Prabhakar et al, 1995;Yang et al, 1998). Several lines of evidence have suggested that CO is synthesized endogenously mainly via the catalysis of heme by heme oxygenase (HO) and functions as a chemical messenger (Maines, 1997;Prabhakar et al, 1995).…”
Section: Introductionmentioning
confidence: 99%